"Pieśni nabożne…" z krakowskiej oficyny Antoniego Wosińskiego (1627) - Wydra, Wiesław (My University, 2012)
The article analyses the unique copy of the old Polish catholic hymn book "Pieśni nabożne na święta uroczyste według porządku Kościoła ś. katolickiego na cały rok z wielką pilnością zebrane" [Songs of piety and devotion...] published in Cracow in 1627 and found at the library at Escorial in Spain. The book, apparently the first known printed Polish catholic extensive hymn book, contained over 140 songs, in Polish and Latin, including works written by Jan Kochanowski and Mikołaj Rej. The article also describes later editions of the hymn book. This is a particularly important book in the history of Polish culture because it was repeatedly republished in different printing offices, not only Catholic, under the same or slightly changed title as late as until the nineteenth century. Numerous editions of the hymn book constitute a valuable source for the study of Polish Catholic hymns as they make it possible to follow and trace the chronology of works, their textual variations and the popularity of particular songs or hymns within a particular time frame, as well as their range of influence and regional occurrence.
“Pieśni nabożne…” from the Cracow-based printing office of Antoni Wosiński (1627)
Keywords: Polish culture; printing in Poland; history of Polish literature; history of the book; Old-Polish religious song